Post-flood impact on the quality of life of victims in East Coast Malaysia - Azmawati Mohammed Nawi; Sharifa Ezat Wan Puteh; Rozita Hod; Idayu Badilla Idris; Izzah Syazwani Ahmad; Qistina Mohd Ghazali (Penerbit Universiti Kebangsaan Malaysia, 2021)
Objective: This study aimed to evaluate the quality of life among flood victims exposed at three worst districts in Pahang, Malaysia. Methods: Semi-guided questionnaires were distributed randomly to a total of 602 flood victims. Quality of life (QOL) was measured using WHO Quality of Life-BREF (WHOQOL-BREF), which were assessed based on four domains, i.e. physical activity, psychological, social relationships and environment. Results: Victims of the flood had a poorer quality of life in all the domains especially physical (59.0%) and psychological (53.3%) domain. The impact of the flood on QOL was higher among women, those who reside in the urban area, the elderlies and persons with high education and income. Conclusion: Flood event has reduced the QOL of victims. The impact of flood has been found to be mitigated over the time and relief efforts. Interventions aimed to reduce these concerns in acute post-flood areas are essential to minimize poor QOL among the affected victims.